Overview of publications on green roof: socio-educational possibilities and community strengthening - Toledo, Lúcio Lorandi de; Toledo, Renata Ferraz de (Revista Nacional de Gerenciamento de Cidades, 2023)
Goal. Identify and present an overview of publications on green roofs, as well as verify and analyze their use in buildings of social interest and in association with socio-educational processes and community strengthening. Methodology. Integrative review, based on “Periódicos Capes, Scielo e Ebsco”, using “green roof”, “living roof” and “green roof” as descriptors, from 2012 to March/2023. Originality/relevance. It sought to update what has been published about green roofs and recognize possibilities of producing new knowledge on the subject, in a collaborative way, directly involving different social actors. Results. A total of 62 publications were analyzed, most by researchers in civil engineering, architecture, urbanism and environmental sciences, developed mainly through experimental field research. The topics were varied, with emphasis on studies on rainwater management, thermal performance, public policies, building structure, technical and economic feasibility. Regarding the use of green roofs in buildings of social interest, teaching institutions, social spaces, housing of social interest and rural settlements were cited, and in the latter, the research encouraged the integration of knowledge through the appropriation of techniques by residents. Theoretical/methodological contributions. The panorama presented contributes to the identification of scientific, theoretical and methodological gaps on the subject, and can help and stimulate new studies. Social and environmental contributions. It highlights the importance of locally-based research, especially in the constructed urban setting, aimed at sustainability, community strengthening and the exercise of citizenship.